2021
DOI: 10.3389/fpsyg.2021.736051
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Continuance Usage of Mobile Learning Applications: The Moderating Role of Habit

Abstract: This study explored the factors that affect the intention of users to continue using mobile learning (m-learning) applications (apps). The influence of habit on user behavior toward information systems has been extensively discussed in the literature, but its role in the continuance of users when it comes to their usage of apps, especially m-learning apps, has rarely been reported. To obtain a comprehensive understanding of behaviors regarding the use of m-learning apps, this study constructed a theoretical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 35 publications
5
10
0
Order By: Relevance
“…However, it is revealed that the additional variables selected should be applied depending on the nature of the technological product used, research situation or time frame, population background, and culture. Lastly, due to the revelation of mediating effect in this study, it also offers a comprehensive understanding of the mechanism that enriches the m-learning application usage apart from complementing prior studies, such as Y. T. Wang and Lin (2021), Ünal and Güngör (2021) and Chang (2022), that simply focus on the direct links of variables without highlighting the role of satisfaction as mediator.…”
Section: Contributionsmentioning
confidence: 91%
“…However, it is revealed that the additional variables selected should be applied depending on the nature of the technological product used, research situation or time frame, population background, and culture. Lastly, due to the revelation of mediating effect in this study, it also offers a comprehensive understanding of the mechanism that enriches the m-learning application usage apart from complementing prior studies, such as Y. T. Wang and Lin (2021), Ünal and Güngör (2021) and Chang (2022), that simply focus on the direct links of variables without highlighting the role of satisfaction as mediator.…”
Section: Contributionsmentioning
confidence: 91%
“…We modified the ECM and SDT as our proposed conceptual model. ECM has also been used in several studies related to the use of applications for learning contexts, such as the research of Luo, Lin, Yang (2021), Ünal dan Güngör (2021), and Wang and Lin (2021). ECM is used in this study to analyze the factors that influence MALL www.ejel.org 301 ISSN 1479-4403 continuance intention while SDT is used to determine the factors that influence motivation and satisfaction with MALL.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Perceived usefulness is defined in this study as the degree of user confidence that MALL can improve their learning performance. Wang and Lin (2021) found that confirmation from users can affect the level of perceived usefulness of users. Their study found that users who realize the achievement of expectations using the application feel that the application will be helpful for the user.…”
Section: Figure 1: Proposed Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotion-related factors are also stressed, such as affection (Dalvi-Esfahani et al, 2020 ; Zhang et al, 2022 ), enjoyment (Ashrafi et al, 2021 ; Huang, 2020 ), and interest (Lu et al, 2019 ). Other internal factors involving flow (Wang & Lin, 2021 ), habit (Dai et al, 2020a ), and hope (Ding, 2019 ) are also underlined. This study mainly investigates the effects of three internal factors—cognitive factors (perceived competition and perceived risk) and curiosity—on continuance intention through emotions in the context of MOOC learning.…”
Section: Introductionmentioning
confidence: 99%